Google inject: increasing engagement with fact-checks through nudging - Konstantinou, Loukas; Karapanos, Evangelos (My University, 2026)
Fact-checking has emerged as a principal part of news reporting with over 400 fact-checking organisations worldwide. However, fewer than one in ten individuals report having used a fact-checking service. In this paper, we introduce Google Inject: a technology-mediated nudge that integrates, relevant to one's query, fact-checks, into the Google search results page. We report on a laboratory study that inquired into how four design variables, in particular, the number of fact-checking articles injected, their positioning, concealment and seamlessness affect users' experience and proximal behaviours with Google Inject. All in all, the paper highlights the complexity and importance of nudge design, as seemingly subtle variations in the design and implementation of a nudge can have a profound impact on its effectiveness.
Keywords: design variations; human-centered computing; nudging; Online misinformation; usability testing